Generation of MicroRNA-34 Sponges and Tough Decoys for the Heart: Developments and Challenges - Bernardo, Bianca C.; Gregorevic, Paul; Ritchie, Rebecca H.; McMullen, Julie R. (Frontiers in Pharmacology, 2018)
Heart failure (HF) is a debilitating and deadly chronic disease, with almost 50% of patients with HF dying within 5 years of diagnosis. With limited effective therapies to treat or cure HF, new therapies are greatly needed. microRNAs (miRNAs) are small non-coding RNA molecules that are powerful regulators of gene expression and play a key role in almost every biological process. Disruptions in miRNA gene expression has been functionally linked to numerous diseases, including cardiovascular disease. Molecular tools for manipulating miRNA activity have been developed, and there is evidence from preclinical studies demonstrating the potential of miRNAs to be therapeutic targets for cardiovascular disease. For clinical application, miRNA sponges and tough decoys have been developed for more stable suppression and targeted delivery of the miRNA of choice. The aim of this study was to generate miRNA sponges and tough decoys to target miR-34 in the mouse heart. We present data to show that using both approaches we were unable to get significant knockdown of miR-34 or regulate miR-34 target genes in the heart in vivo. We also review recent applications of this method in the heart and discuss further considerations for optimisation in construct design and testing, and the obstacles to be overcome before they enter the clinic.